Physiological basis of Lance Armstrong`s Tour de France performances - Kearney, J. T. (2005)
Optimal Performance Is Complex and Multifaceted Attempts have been made to challenge the performances of Armstrong based on the calculation of an array of isolated variables. A performance as complex as the Tour de France can not be dissected based on the analysis of single determinants of performance. The basis of this tutorial review of factors relevant to performance is a model by Seiler, however, multiple other similar models could be employed.